The Method of Prime Costs Determination of the Model Row Goods - Barashkov, A. S. S.; Petrosian, D. S. S. (Nonlinear Analysis: Modelling and Control, 2008)
The concept of the model row goods is introduced. These are the interchangeable goods differing by quality and price. Cognacs of various vintage years produced on one cognac factory are a typical example of such goods. For the indicated kind of the goods the method of the cost price determination of the goods of competitors is worked out and realized. The initial information for determination is the data on the prices of the goods and sales volumes.